Refractories for Aluminum : Electrolysis and the Cast House - Yurkov, Andrey (Springer International Publishing : Imprint: Springer, 2017)
This book details the rigorous requirements for refractories designed for aluminium metallurgical processes: reduction, cast house, and anode production. The author describes requirements specific to the properties and structure of refractory materials that differentiate it from the refractories for ferrous metallurgy, among others. A comparison is drawn between the properties and structure of refractories and carbon cathode materials from different points of view: from the perspective of physical chemistry and chemical interactions during the metallurgical process and from the aspect of designing reduction pots and furnaces to accommodate the lifetime of metallurgical aggregates that are a part of aluminum refractory processes.
Keywords: Materials science.; Physical chemistry.; Building materials.; Metals.; elektronické knihy; electronic books